Healthcare workers as a sentinel surveillance population in the early phase of the COVID-19 pandemic - Indumathi Venkatachalam; Edwin Philip Conceicao; May Kyawt Aung; Molly Kue Bien How; Liang En Wee; Jean Xiang Ying Sim; Ban Hock Tan; Moi Lin Ling (Singapore Medical Journal)
Introduction: Healthcare workers (HCWs) are a critical resource in the effort to control the COVID-19 pandemic. They are also a sentinel surveillance population whose clinical status reflects the effectiveness of the hospital’s infection prevention measures in the pandemic. Methods: This was a retrospective cohort study conducted in Singapore General Hospital (SGH), a 1,822-bed tertiary hospital. Participants were all HCWs working in SGH during the study period. HCW protection measures included clinical workflows and personal protective equipment developed and adapted to minimise the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. HCW monitoring comprised staff contact logs in high-risk locations, twice-daily temperature monitoring, assessment of HCWs with acute respiratory illnesses (ARIs) in the staff clinic and, in the event of an exposure, extensive contact tracing, detailed risk assessment and risk-based interventions. HCW surveillance utilised monitoring data and ARI presentations and outcomes. Results: In the ten-week period between 6 January 2020 and 16 March 2020, 333 (17.1%) of 1,946 HCWs at risk of occupational COVID-19 presented with ARI. 32 (9.6%) screened negative for SARS-CoV-2 from throat swabs. Five other HCWs developed COVID-19 attributed to non-clinical exposures. From the nine COVID-19 exposure episodes investigated, 189 HCW contacts were identified, of whom 68 (36.2%) were placed on quarantine and remained well. Conclusion: Early in an emerging infectious disease outbreak, close monitoring of frontline HCWs is essential in ascertaining the effectiveness of infection prevention measures. HCWs are at risk of community disease acquisition and should be monitored and managed to prevent onward transmission.